Introduction to finite W-algebras (2016)
These are notes of lectures given at UN Encuentro 2016 at the Universidad Nacional de Colombia. We begin with the definition of infinite W-algebras. Then we explain the motivation for the definition if finite W-algebras. Then we present basic facts about the structure and representations of finite W-algebras. In these lectures we follow the historical development of the subject.